Analisis Pengendalian Persediaan Bahan Baku dengan Metode Economic Order Quantity pada PT. Enggal Subur Kertas (Management Analysis Journal, 2015)
Optimal inventory within the company is one of the important factors in the performance of the company. Optimal inventory in this study is determined by Economic Order Quantity (EOQ) method. EOQ is used in solving problems of this company because the result of calculation is more accurate. This research belongs to quantitative and it is used to study thoroughly the application of Economic Order Quantity (EOQ) of raw materials in inventory control at PT. Enggal SuburKertas. Object of this research is the amount of inventory, the amount of the purchase, the amount pf raw material that used for the production process, and ordering and storage costs of raw materials. The result of this research show that the calculation of TIC using Economic Order Quantity method is more optimal than conventional method, so this company can save costs about 74,26% for afval box, 30,13% afval cones, and 40,01% for afval marga.